2006
DOI: 10.1186/cc4840
|View full text |Cite
|
Sign up to set email alerts
|

Lung and 'end organ' injury due to mechanical ventilation in animals: comparison between the prone and supine positions

Abstract: Introduction Use of the prone position in patients with acute lung injury improves their oxygenation. Most of these patients die from multisystem organ failure and not from hypoxia, however. Moreover, there is some evidence that the organ failure is caused by increased cell apoptosis. In the present study we therefore examined whether the position of the patients affects histological changes and apoptosis in the lung and 'end organs', including the brain, heart, diaphragm, liver, kidneys and small intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 42 publications
1
4
0
3
Order By: Relevance
“…In the prone position, the transpulmonary pressure in dorsal lung areas increases, opening alveoli and improving gas-exchange [ 22 ]. Some authors have reported that in healthy [ 23 ], as well as in lung-injured animals [ 24 ], mechanical ventilation leading to lung overdistension and cyclic collapse/reopening was associated with less extensive histological change in dorsal regions in the prone, as compared to the supine position. Although the claim that body position affects the distribution of lung injury has been challenged, the development of VILI due to excessively high V T seems to be delayed during prone compared to supine positioning [ 25 ].…”
Section: Definition and Factors Affecting Recruitment Maneuversmentioning
confidence: 99%
“…In the prone position, the transpulmonary pressure in dorsal lung areas increases, opening alveoli and improving gas-exchange [ 22 ]. Some authors have reported that in healthy [ 23 ], as well as in lung-injured animals [ 24 ], mechanical ventilation leading to lung overdistension and cyclic collapse/reopening was associated with less extensive histological change in dorsal regions in the prone, as compared to the supine position. Although the claim that body position affects the distribution of lung injury has been challenged, the development of VILI due to excessively high V T seems to be delayed during prone compared to supine positioning [ 25 ].…”
Section: Definition and Factors Affecting Recruitment Maneuversmentioning
confidence: 99%
“…Finally, the physiological changes produced during the use of the mechanical ventilator cause stress at the lung, but can also affect distant organs. Therefore, mechanical ventilators could produce functional alterations and even injuries in heart, liver, kidney and brain [ 49 , 50 ]. For this reason, and as a final outcome, the post-mortem analysis certified the absence of both acute tissue damage and barotrauma signals due to the use of Masi.…”
Section: Resultsmentioning
confidence: 99%
“…Αυτό επιτυγχάνεται με κατάλληλη ρύθμιση δυο βασικών παραμέτρων που διέπουν τον μηχανικό αερισμό: επεμβατικός αερισμός επιτυγχάνεται με τη βοήθεια τεχνητού αεραγωγού μέσω του οποίου εξασφαλίζεται η απρόσκοπτη πρόσβαση στους φυσικούς αεραγωγούς, δεν απαιτεί την συνεργασία του ασθενούς και μπορεί να εφαρμοστεί και παθητικά.Κατά τον μη επεμβατικό αερισμό ο φυσικός αεραγωγός ελέγχεται από τον ασθενή και επομένως απαιτείται η συνεργασία του, ενισχύει την αντλητική ικανότητα του πνεύμονα και εφαρμόζεται με την βοήθεια αεροστεγώς εφαρμοζόμενων μασκών74 . μεγάλη τεχνολογική πρόοδος, η τεχνογνωσία των αναπνευστήρων, καθώς και η πρόοδος της παθοφυσιολογίας της αναπνευστικής ανεπάρκειας βοήθησαν στο να δημιουργηθούν πολλά μοντέλα αερισμού ώστε να προσαρμόζονται απόλυτα στις ανάγκες των βαρέως πασχόντων ασθενών77 . Τελοεισπνευστική Στατική Πίεση (Pplateau), δηλαδή η σταθερή πίεση που ασκείται στις κυψελίδες και τους μικρούς αεραγωγούς κατά το μηχανικό αερισμό θετικών πιέσεων, να είναι πάντοτε μικρότερη από 30cmH 2 O, προκειμένου να αποφευχθούν βλάβες του πνεύμονα από υψηλές πιέσεις (βαροτραύματα  )77 .…”
unclassified
“…μεγάλη τεχνολογική πρόοδος, η τεχνογνωσία των αναπνευστήρων, καθώς και η πρόοδος της παθοφυσιολογίας της αναπνευστικής ανεπάρκειας βοήθησαν στο να δημιουργηθούν πολλά μοντέλα αερισμού ώστε να προσαρμόζονται απόλυτα στις ανάγκες των βαρέως πασχόντων ασθενών77 . Τελοεισπνευστική Στατική Πίεση (Pplateau), δηλαδή η σταθερή πίεση που ασκείται στις κυψελίδες και τους μικρούς αεραγωγούς κατά το μηχανικό αερισμό θετικών πιέσεων, να είναι πάντοτε μικρότερη από 30cmH 2 O, προκειμένου να αποφευχθούν βλάβες του πνεύμονα από υψηλές πιέσεις (βαροτραύματα  )77 . Σε αυτό το μοντέλο αερισμού, η πίεση του αναπνευστήρα ρυθμίζεται ώστε να επιτυγχάνεται ο επιθυμητός αναπνεόμενος όγκος, ο οποίος εξαρτάται βεβαίως τόσο από τις πνευμονικές αντιστάσεις και την ενδοτικότητα του αναπνευστικού συστήματος του ασθενούς, όσο και από τον χρόνο της εισπνοής.…”
unclassified
See 1 more Smart Citation